Reviving health promotion in South Australia: The role of ideas, actors and institutional forces. (11th November 2022) - Musolino, Connie; van Eyk, Helen; Freeman, Toby; Fisher, Matt; MacDougall, Colin; Williams, Carmel; Baum, Fran
Abstract: Globally health promotion has remained marginalized while biomedical health systems have maintained and even increased their dominance. During 2019–2021 we drew on the local and historical knowledge of actors from multiple sectors through semi-structured interviews and focus groups, to assess the implications of the withdrawal of the state from health promotion in a suburban region of South Australia. Institutional theory enabled in-depth analysis of the ideas, actors, and institutional forces at play in the institutional field, and how these elements come together to maintain the dominance of medicine. We found that the ideas, actors and institutional forces supporting health promotion in the study region have weakened and fragmented. This has happened as biomedicine has increased its dominance in the region's health system, mirroring international trends. The results point to a withdrawal of state and federal governments from health promotion, which has led to severe gaps in leadership and governance, and locally, to a decline in capacity and resources. The state health department reallocated resources to focus on individual behavioural change rather than more structural factors affecting health. While some activities aimed at the social determinants of health or community development strategies remained, these had minimal institutional support. The establishment of a state government wellbeing agency in 2020 prompted an exploration to determine whether the agency and the international wellbeing movement presents an opportunity for a revival of more comprehensive health promotion. Lay Summary: Health promotion has a rich history in South Australia. However, since government withdrew funding and institutional support, health promotion has become increasingly fragmented, unco-ordinated and targeted towards individual behaviour change activities. Analysis of the role of ideas, actors, and institutional forces, such as government policies, found that biomedical approaches to health and health care increasingly dominate the health system and health policy environment in the state and Australia wide. The establishment of a state government wellbeing agency in 2020 prompted optimism from participants that the government may once again take a leadership role in reviving health promotion and prevention strategies.